Latent transforming growth factor‐β binding proteins (LTBP‐1 and LTBP‐2) and gingiva keratinization. (28th April 2015) - Chiang, M‐S; Yang, J‐R; Liao, S‐C; Hsu, C‐C; Hsu, C‐W; Yuan, K
<x xml:space="preserve">Abstract</x> Objective Transforming growth factor‐beta (TGF‐β) proteins are involved in epithelial keratinization. The major function of latent TGF‐β binding proteins (LTBPs) is modulating TGF‐β activity. However, whether LTBP‐1 and LTBP‐2 play roles in gingiva keratinization remains unclear. Materials and Methods Human keratinized gingiva and non‐keratinized alveolar mucosa were processed for LTBP‐1, LTBP‐2, cytokeratin‐1 (K1), cytokeratin‐4 (K4), and TGF‐β immunohistochemical (IHC) staining. Porcine heterotopically transplanted connective tissues and newly grown epithelia were harvested for IHC staining. The expression levels of LTBP‐1 and LTBP‐2 were compared between differentiated and undifferentiated human normal oral keratinocytes (hNOK). The expression of LTBP‐1 and LTBP‐2 was knocked down in a cell line (OEC‐M1) to evaluate the effects on the expression of K1, K4, and involucrin (INV). Results In human and porcine specimens, LTBP‐2 expression patterns distinguished keratinized and non‐keratinized oral epithelia. Western blotting results showed that K1, LTBP‐1, and INV proteins were upregulated in differentiated hNOK. In OEC‐M1 cells, LTBP‐2 knockdown resulted in upregulated the expression of K1 and INV and downregulated the expression of K4. LTBP‐1 knockdown resulted in opposite effects. Conclusion The expression patterns of LTBP‐2 differ in keratinized gingiva and non‐keratinized mucosa. LTBP‐1 and LTBP‐2 are involved in the keratinization of oral epithelium; however, the underlying mechanism remains to be elucidated.